2022
DOI: 10.1038/s41467-022-28519-x
|View full text |Cite
|
Sign up to set email alerts
|

Charge-noise spectroscopy of Si/SiGe quantum dots via dynamically-decoupled exchange oscillations

Abstract: Electron spins in silicon quantum dots are promising qubits due to their long coherence times, scalable fabrication, and potential for all-electrical control. However, charge noise in the host semiconductor presents a major obstacle to achieving high-fidelity single- and two-qubit gates in these devices. In this work, we measure the charge-noise spectrum of a Si/SiGe singlet-triplet qubit over nearly 12 decades in frequency using a combination of methods, including dynamically-decoupled exchange oscillations w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 56 publications
4
32
1
Order By: Relevance
“…The charge noise shows a standard deviation of 0.27 μeV/√Hz with the average of 0.61 μeV/√Hz and several points lower than 0.1 μeV/√Hz. This is the state-of-the-art low charge noise for MOS devices 8,[32][33][34] , and comparable to SiGe heterostructures 28,29,31,51 .…”
Section: Charge Noisementioning
confidence: 90%
See 2 more Smart Citations
“…The charge noise shows a standard deviation of 0.27 μeV/√Hz with the average of 0.61 μeV/√Hz and several points lower than 0.1 μeV/√Hz. This is the state-of-the-art low charge noise for MOS devices 8,[32][33][34] , and comparable to SiGe heterostructures 28,29,31,51 .…”
Section: Charge Noisementioning
confidence: 90%
“…To study the device noise, we focus on the SET charge noise as it has been shown to well represent the qubit noise , and typically the noise figure at 1 Hz is used as the metric to benchmark between different structures and material platforms [28][29][30] . On the flank of the Coulomb peak, where the SET is the most sensitive to environmental noise, we record the current noise spectrum.…”
Section: Charge Noisementioning
confidence: 99%
See 1 more Smart Citation
“…Multi-qubit gate fidelities are mainly limited by charge noise though, which causes fluctuations in the voltage [3,4,[53][54][55][56][57][58]. As a result, the exchange strength, J, fluctuates in the presence of charge noise because it depends on the voltage.…”
Section: Smooth Pulses Using Dynamical Invariantsmentioning
confidence: 99%
“…The SET spectroscopy data is valuable in understanding the amplitude of the electrical noise present in the system, by probing directly the charge fluctuations via the SET, and will be useful especially for probing low frequency charge noise [52]. It is also a fast measurement that can be used as a benchmarking tool for noise in qubit systems, without performing a full qubit noise spectroscopy [53]. Although it is not capable of probing noise in the high frequency regime, the results from the studies here indicate that extrapolating the low frequency results to higher frequencies is consistent with the qubit coherence results, and therefore remains a useful predictive tool.…”
Section: (C) (Purple Trace)mentioning
confidence: 99%